Study of permeability of saturated homogeneous and heterogeneous porous media (2008)
Many practical seepage and drainage problems can be studied by constructing flow nets for section with a single permeability, however, many natural soil deposits are more or less stratified, often with horizontal bedding that make horizontal permeabilities much greater than the vertical. Three different types of heterogeneous media from five soil sample of different porosities were considered: with constant-head permeameter to determine the saturated hydraulic conductivity for each. The result shows that least permeable medium dominates in the permeability of heterogeneous medium than layered heterogenous medium. However, fluid flow in homogeneous porous media is generally faster than that of heterogeneous medium of similar geometry and grains packing. Therefore, the effect of least permeable unit in heterogeneous medium must be considered in selecting a proper filter for seepage control.